2022
DOI: 10.1186/s12991-022-00397-z
|View full text |Cite
|
Sign up to set email alerts
|

The grief experience during the COVID-19 pandemic across different cultures

Abstract: Grief is the physical or mental suffering experienced after a major loss, usually the death of a loved one. It is a universal experience, but sociocultural factors, such as cultural or ethnic identity and religious beliefs predict and shape the expression of grief. The circumstances under which people are experiencing grief during the coronavirus outbreak have adversely affected the grieving process. Unexpected deaths, social distancing rules and visitor restrictions in healthcare facilities have posed a heavi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
17
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 9 publications
1
17
0
2
Order By: Relevance
“…In Iran there is also several subcultures but generally continuous presence of people around survivors in early days of grief, is among important factors of effective social support. Consistent with the previous literature, the themes of this study showed that this effective social support has been reduced (8).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…In Iran there is also several subcultures but generally continuous presence of people around survivors in early days of grief, is among important factors of effective social support. Consistent with the previous literature, the themes of this study showed that this effective social support has been reduced (8).…”
Section: Discussionsupporting
confidence: 91%
“…Much research has shown that exposure to this pandemic has raised the risk of complicated grief caused by the fact that this infectious disease has been unknown and unpredictable, a lack of specific and efficient treatment to control and eradicate it, the continuity of the quarantine, the lack of the possibility to hold mourning rituals or funerals, the lack of the opportunity to be present in the ceremonies, strict laws of transportation, the mortality and morbidity of the virus, ICU staff 's work environment that sometimes caused the risk of spreading the virus and even multiple fatalities in a family cluster in a short period (6)(7)(8).…”
Section: Introductionmentioning
confidence: 99%
“…Three years after the global coronavirus pandemic outbreak, its severe and manifold consequences have been largely demonstrated not only in terms of global economy, culture, society, and general health, but also mental health (1)(2)(3). Many aspects of daily life have been affected by the lockdown and social distancing measures, further filtered by individual factors, as well as specific sociocultural dynamics, including norms, values, and religions (4)(5)(6)(7)(8).…”
mentioning
confidence: 99%
“…The lockdown and social distancing measures have intensified these issues, particularly for vulnerable individuals, also influencing the delivery of mental health interventions (4). Moreover, the impact of the pandemic has varied across different sociocultural groups, influenced by norms, values, and religions (5)(6)(7). This highlights the need to consider not only medical and scientific aspects but also the broader societal and cultural dynamics in addressing public health crises.…”
mentioning
confidence: 99%